State of Post-injury First Response Systems in Nepal—A Nationwide Survey - Banstola, Amrit; Smart, Gary; Raut, Raju; Ghimire, Krishna Prasad; Pant, Puspa Raj; Joshi, Prerita; Joshi, Sunil Kumar; Mytton, Julie (Frontiers in Public Health, 2021)
Injuries account for 9.2% of all deaths and 9.9% of the total disability-adjusted life years in Nepal. To date, there has not been a systematic assessment of the status of first response systems in Nepal. An online survey was cascaded through government, non-governmental organisations and academic networks to identify first response providers across Nepal. Identified organisations were invited to complete a questionnaire to explore the services, personnel, equipment, and resources in these organisations, their first aid training activities and whether the organisation evaluated their first response services and training. Of 28 organisations identified, 17 (61%) completed the questionnaire. The range of services offered varied considerably; 15 (88.2%) provided first aid training, 9 (52.9%) provided treatment at the scene and 5 (29.4%) provided full emergency medical services with assessment, treatment and transport to a health facility. Only 8 (47.1%) of providers had an ambulance, with 6 (35.3%) offering transportation without an ambulance. Of 13 first aid training providers, 7 (53.8%) evaluated skill retention and 6 (46.2%) assessed health outcomes of patients. The length of a training course varied from 1-16 days and costs from US4.0 to US430.0 per participant. There was a variation among training providers in who they train, how they train, and whether they evaluate that training. No standardisation existed for either first aid training or provision of care at the scene of an injury. This survey suggests that coordination and leadership will be required to develop an effective first response system across the country.